Estimation and management of shrimp processing waste in organised shrimp processing sector in India: Opportunities and challenges - C. G. Joshy; K. Elavarasan; V. Renuka; B. Madhusudana Rao; K. V. Premdev; A. A. Zynudheen; Ninan, George (Indian Journal of Fisheries, 2023)
This study was conducted to estimate the magnitude of processing waste produced in the organised shrimp processing sector of India in order to assess the opportunities available for its utilisation. The estimation of magnitude of shrimp processing waste was based on secondary data and its management was based on primary data collected through surveys at processing plants. The organised shrimp processing sector in India generated a large volume of shrimp processing waste at a growth rate of 12% during 2000-2018. The quantity of shrimp processing waste generated ranged from 1.2 to 4.6 lakh t, which can be utilised to produce 6712 to 27453 t of chitin alone. However, our study indicated that 75% of the total waste generated remained either unused or managed unscientifically, even when there is huge demand for chitin and its derivatives in the domestic as well as in the international market. The case studies from chitin producing plants revealed that some costs were incurred in the procurement of shrimp processing waste as a secondary raw material for the production of chitin. Thus forming a link between shrimp processing plants and chitin and its derivatives producing plants would improve the supply of quality raw material and improve utilisation of processing wastes. The number of chitin and its derivatives producing plants are too few in India to fully accommodate the large volume of shrimp processing waste generated every year. Therefore, infrastructure development in the chitin and associated industry with active support from government organisations to overcome the burden of initial investment is needed urgently, which can in turn encourage entrepreneurship development in the sector for diversified applications. Keywords: Chitin, Chitosan, Glucosamine hydrochloride, Growth rate, Waste utilisation